Development of digital literacy assessment instrument for prospective teacher students in higher education - Kantona, Hari; Munadi, Sudji (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2024)
This study aims to (1) develop an instrument to assess digital literacy skills among prospective teacher students, (2) examine its psychometric quality, and (3) describe students' digital literacy levels. The instrument development followed ten stages, including item writing, expert review, limited and large-scale testing, and data analysis. A total of 262 prospective teachers from UNY and UIN Sunan Kalijaga Yogyakarta participated in the large-scale test. Construct validity was tested using confirmatory factor analysis (CFA), and item characteristics were analyzed using the graded response model (GRM) within item response theory (IRT). Reliability was measured using Cronbach's Alpha. The final instrument contains 35 items across seven aspects: information literacy, digital scholarship, learning skills, ICT literacy, career and identity management, communication and collaboration, and media literacy. The instrument showed good psychometric quality based on Aiken's V, CFA, and IRT analysis. Measurement results showed 9% of students had excellent digital literacy, 19% good, 38% sufficient, 30% lacking, and 4% very lacking. These results highlight the need for targeted training and support to improve digital literacy among prospective teachers in Yogyakarta.